Understanding the effect of social media marketing activity for promoting intention to participate in martial arts - Xie, Ming-Chuan; Chang, Yao-Chuan; Cai, Chuan-Ming (Frontiers in Psychology, 2022)
The development of folk martial arts in China has encountered many obstacles and difficulties in promoting the sport. Although there are many martial arts-related groups on WeChat, the largest social media in China, the interaction is not enthusiastic enough and the participation is too low. To improve the effectiveness of social media marketing and promotion of martial arts, this study used WeChat martial arts group users as the target population. The social media marketing activities and user experiences were used as independent variables to analyze their effects on martial arts attachment, attitudes toward martial arts, subjective norms, and intention to participate in martial arts. Descriptive statistics, reliability analysis, variance analysis, and regression analysis were conducted to explore the associated factors of this study. The results of the study showed that social media marketing activities and user experience had a positive and significant effect on martial arts attitudes, subjective norms, and martial arts attachment. Martial arts attitudes, subjective norms, and martial arts attachment had a positive and significant effect on the intention to participate. Finally, based on the results of this study, we propose recommendations for social media marketing activities, user experience, martial arts attachment, attitudes toward martial arts, subjective norms, and martial arts participation intentions for martial arts social media operators, martial arts promotion organizations, and subsequent studies.